TRAINING OF TEACHERS FOR THE EARLY CHILDHOOD EDUCATION IN THE PEDAGOGY COURSE: REFLECTIONS FROM THE ANALYSIS OF SCIENTIFIC PRODUCTION (2002-2013) - Oliveira, Daniele Ramos de [UNESP]; Galdi da Silva, Rosangela Aparecida [UNESP]; Guimaraes, Celia Maria [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
This article discusses the issue of teacher training for early childhood education and summarizes trends in Brazilian theses and dissertations about the training in the pedagogy course. Considering this objective, we contextualize briefly the history of the training of early childhood education teachers to identify which issues are challenging. The bibliographic mapping of Brazilian academic research focused on initial teacher training for early education in the pedagogy course, published between 2002 and 2013, was held in the database in the Brazilian Digital Library of Theses and Dissertations (BDTD). This survey identified aspects that may be constituted as contributions to public policies and trainers of early childhood teachers. The analysis revealed the precariousness of the training for teachers of early childhood education. The studies suggest that the pedagogy course does not provide the knowledge necessary for teachers to choose appropriate referrals to education of young children to perform their duty to care-educate. Similarly, it compromises the invention of a profession: the Early Childhood professional. This scenario calls for urgent efforts for integrated training for future professional practice through projects that combine initial and continuing training.
Keywords: Childhood Education; Public policy; Pedagogy course; Training; Supervision